2018
DOI: 10.1007/s00125-018-4591-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of slow progression to diabetes in multiple islet autoantibody-positive individuals from five longitudinal cohorts: the SNAIL study

Abstract: Aims/hypothesis Multiple islet autoimmunity increases risk of diabetes, but not all individuals positive for two or more islet autoantibodies progress to disease within a decade. Major islet autoantibodies recognise insulin (IAA), GAD (GADA), islet antigen-2 (IA-2A) and zinc transporter 8 (ZnT8A). Here we describe the baseline characteristics of a unique cohort of 'slow progressors' (n = 132) who were positive for multiple islet autoantibodies (IAA, GADA, IA-2A or ZnT8A) but did not progress to diabetes within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…In our study, we identified a subset of participants with low risk of progression based on age, autoantibody type and metabolic status. In comparison, using a combination of birth and screened cohorts across a broad age range but a smaller sample size, Long et al [36] did not demonstrate autoantibody differences in individuals characterised as slow progressors (diabetes-free 10 years after mAb determination). The Diabetes in Autoimmunity Study in the Young (DAISY) birth cohort identified mAb-positive slow progressors that were set apart from rapid progressors by IAA titre and the rate of progression from single to mAb positivity [7].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, we identified a subset of participants with low risk of progression based on age, autoantibody type and metabolic status. In comparison, using a combination of birth and screened cohorts across a broad age range but a smaller sample size, Long et al [36] did not demonstrate autoantibody differences in individuals characterised as slow progressors (diabetes-free 10 years after mAb determination). The Diabetes in Autoimmunity Study in the Young (DAISY) birth cohort identified mAb-positive slow progressors that were set apart from rapid progressors by IAA titre and the rate of progression from single to mAb positivity [7].…”
Section: Discussionmentioning
confidence: 92%
“…Of 36 slow progressors identified in the BOX study, confirmed as multiple islet autoantibody positive using current harmonised assays [2], 19 were not included in the current analysis: 11 were excluded because they developed diabetes more than 10 years after the initial serum sample (and no follow-up serum sample was available after the 10 year point before they had developed diabetes); seven were lost to follow-up; and one had chronic lymphocytic leukaemia.…”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal studies of at-risk individuals have shown, however, that up to 30% of people positive for multiple autoantibodies do not progress to type 1 diabetes within 10 years [1]. Such individuals were recruited to the Slow or Non-progressive Autoimmunity to the Islets of Langerhans (SNAIL) study from five other cohort studies, including the Bart's Oxford Family Study (BOX) [2]. All four major autoantibodies, specific for GAD (GADA), islet antigen-2 (IA-2A), insulin (IAA) and zinc transporter 8 (ZnT8A), were found in these slow progressors to type 1 diabetes (hereafter referred to as 'slow progressors').…”
Section: Introductionmentioning
confidence: 99%
“…IAA as the first autoantibody peaks during the second year of life, while GADA reactivity tends to appear later, and with a considerably lower and broader peak (35)(36)(37). Individuals testing positive for multiple autoantibodies but remaining unaffected for ≥10 years after the seroconversion are frequently GADA positive in their first sample positive for multiple autoantibodies (38). As the T1D-linked Coxsackievirus B1 infections have been associated with the appearance of IAA as the first autoantibody, but not with initial GADA positivity (39), the current observations support the idea that the triggers of the autoimmune process may be heterogeneous.…”
Section: Advance Articlementioning
confidence: 99%